The Effect of Principal Leadership Style, Work Motivation, and Professional Competence of Primary School Teacher Performance in Kendari City - Ridwan Yusuf Deluma; Zulela MS; Moch Asmawi (JETL (Journal of Education, Teaching and Learning), 2020)
This study aimed to determine the effect of the principal's leadership style, motivation, and professional competence on the performance of an elementary school teacher in the town of Kendari. The design of this research was path analysis. The study samples were 241 primary school teachers and they were taken by using a simple random sampling technique. Data were collected by questionnaire and analyzed statistically using path analysis with the program Linear Structural Relations (LISREL). The professional competence was equal ρy23 = 0.389, t = 4.751, table = 1,97 means t> t table, then H0 was rejected and H1 was accepted The results showed that: (1) there was a positive direct influence between headmaster leadership style to the performance of primary school teachers in the city of Kendari, (2) there was a direct positive influence between work motivation on the performance of primary school teachers in the city Kendari. The conclusion of this research are: (1) There is a positive direct influence on the performance of the leadership style of primary school teachers in Kendari; (2) There is a positive direct influence on the performance of work motivation of primary school teachers in Kendari; (3) There is a positive direct influence on the performance of the professional competence of primary school teachers in Kendari; (4) There is a positive direct influence on the performance of motivational leadership style work in Kendari; (5) There is a positive direct influence leadership style to the professional competence of teachers of primary schools in Kendari.